The Existence of Local Specialties as a Support for Tourism in North Bali - Made Suardani; Luh Linna Sagitarini (Politeknik Negeri Bali, 2020)
ABSTRACT This study is titled the existence of local specialties as a culinary support for tourism in North Bali. So far, tourists only know a few tourist areas in Bali such as Badung, Denpasar and Ubud. Gradually as now tourists have begun to glance at the tourism potential in the North Bali region. As we know, tourists who come to visit there, they are not only to enjoy the panorama of natural and cultural Attractions offered there, but Also wish to taste the special foods in there. Also There are many tourists who eat with the intention of getting to know and taste local specialties from the area, more over, the which has Become a food icon in the area. The purpose of this study was to Determine the existence of North Bali local specialties roomates are still searching for after by customers and foreign tourists. There are many types of food from appetizers to desserts, but Belayag and Siobak are still an icon of North Balinese specialties. This research was conducted using primary and secondary data. This Data collected through observation, interviews, questionnaires, reports related to employees. After the the data is collected, the Data will be Analyzed with descriptive qualitative method. This analysis is used to describe the information Obtained during the research. The results of this study are expected to be used as a reference for Siobak and Belayag food managers as additional information about Siobak and Belayag business opportunities that can be used as a culinary businesses to support tourism development in North Bali. The results of this study can also be used as a reference for the archipelago and Processing Processing cuisine Continental cuisine of teaching materials in the Program in Hospitality and Tourism Business Management Program at the Bali State Polytechnic.